2017
DOI: 10.13005/ojc/330458
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Isopropyl Alcohol in the Properties of Sudanese Reformat Gasoline

Abstract: The role of isopropyl alcohol in the properties of Sudanese reformat gasoline (produced by the refinery located at Algily, Khartoum North city, in Sudan) was studied. The properties of the reformat gasoline which were investigated include , distillation, sulfur content, density, vapor pressure, oxidation stability, copper strip corrosion, gum existence, lead content, and the octane number .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…The characteristic frequency changes depending on the density of the sample. Through a precise determination of the characteristic frequency and a mathematical conversion, the density of the sample was measured [38].…”
Section: Physico-chemical Parameters Of Diesel Fuel Density Of Diesel Fuelmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristic frequency changes depending on the density of the sample. Through a precise determination of the characteristic frequency and a mathematical conversion, the density of the sample was measured [38].…”
Section: Physico-chemical Parameters Of Diesel Fuel Density Of Diesel Fuelmentioning
confidence: 99%
“…The density was calculated from the quotient of the period of oscillations of the U-Tube and the reference oscillator [38]:…”
Section: Physico-chemical Parameters Of Diesel Fuel Density Of Diesel Fuelmentioning
confidence: 99%
See 2 more Smart Citations
“…The properties of gasoline blends with propanol were less investigated, by far. The result of the addition of i-propanol to gasoline consisted in the decrease of the initial and final boiling point, and of the vapor pressure [18]. It is found that much of these studies have given little importance to the chemical composition of gasoline.…”
Section: Introductionmentioning
confidence: 99%